Comments on the section “Cardiovascular risk estimation” in the 2021 European Society of Cardiology guidelines on cardiovascular disease prevention in clinical practice - S. A. Shalnova (Кардиоваскулярная терапия и профилактика, 2022)
The article discusses a new approach to assessing cardiovascular risk in clinical practice, presented in the European guidelines 2021. Two novel risk charts (SCORE2 and SCORE2-OP) have been proposed that have undergone significant revision and require significant changes in primary care practice. It has been suggested that in modern conditions their practical introduction is premature, since the healthcare system is not ready for renewal. Therefore, time is needed to adapt it to the practical healthcare conditions and to revise the medical screening protocols, which will require financial costs. The implementation of these recommendations should be taken responsibly so as not to harm the existing system of preventive care.